Tracing generators' output in transmission open access - Mohd Herwan, Sulaiman; Omar, Aliman; Mohd Wazir, Mustafa; Ismail, Daut (Institute of Electrical and Electronics Engineering (IEEE), 2009)
Link to publisher's homepage at http://ieeexplore.ieee.org